Cellular and molecular effects of nonreciprocal chromosome translocations in Saccharomyces cerevisiae - Nikitin, Dmitri (National Academy of Sciences, 2008)
Saccharomyces cerevisiae strains harboring a nonreciprocal, bridge-induced translocation (BIT) between chromosomes VIII and XV exhibited an abnormal phenotype comprising elongated buds and multibudded, unevenly nucleated pseudohyphae. In these cells, we found evidence of molecular effects elicited by the translocation event and specific for its particular genomic location. Expression of genes flanking both translocation breakpoints increased up to five times, correlating with an increased RNA polymerase II binding to their promoters and with their histone acetylation pattern. Microarray data, CHEF, and quantitative PCR confirmed the data on the dosage of genes present on the chromosomal regions involved in the translocation, indicating that telomeric fragments were either duplicated or integrated mostly on chromosome XI. FACS analysis revealed that the majority of translocant cells were blocked in G(1) phase and a few of them in G(2). Some cells showed a posttranslational decrease of cyclin B1, in agreement with elongated buds diagnostic of a G(2)/M phase arrest. The actin1 protein was in some cases modified, possibly explaining the abnormal morphology of the cells. Together with the decrease in Rad53p and the lack of its phosphorylation, these results indicate that these cells have undergone adaptation after checkpoint-mediated G(2)/M arrest after chromosome translocation. These BIT translocants could serve as model systems to understand further the cellular and molecular effects of chromosome translocation and provide fundamental information on its etiology of neoplastic transformation in mammals.